One Shot! Football & Art Contemporain - Casielles, Nancy; Rollin, Pierre-Olivier; B.P.S.22, Charleroi (Charleroi : B.P.S.22 Charleroi, 2010)
Agirregoikoa, Juan Pérez ; Anekawa, Taku ; Braschler, Mathias ; Fischer, Monika ; Buchanan, Roderick ; Canevari, Paolo ; Castro, Jota ; Chatelain, Joseph ; Christie, Cedric ; Closky, Claude ; Contreras, Freddy ; Costard, Hellmuth ; Dabernig, Josef ; Dandoy, Laurent ; Davies, Robert ; Dean, Stephen ; De Keyser, Raoul ; Delvoye, Wim ; Democracia ; Denis, Marie ; Deutschbauer, Julius ; Everaert, Patrick ; Fatmi, Mounir ; Fontaine, Thierry ; Furlan, Massimo ; Geers, Kendell ; Gordon, Douglas ; Parreno, Philippe ; Gursky, Andreas ; Henry, Julie ; Lagomarsino, Runo ; Lüscher, Ingeborg ; Lüscher, This ; Mareschal, Laurent ; Mastrovito, Andrea ; Merino, Eugenio ; Monge, Priscilla ; Motti, Gianni ; Perbos, Laurent ; The Plug ; PSJM ; Ransonnet, Jean-Pierre ; Rodriguez, Javier ; Schwartz, Pierre ; Swennen, Walter ; Tayou, Pascale Marthine ; Tzaig, Uri ; Van Parys, Yoann ; van Warmerdam, Marijke ; Zgraggen, Maria
Biog. per kunstenaar
Publication à l'occasion de l'exposition 'One Shot! Football & Art Contemporain' au B.P.S.22 à Charleroi, 06.03.2010-11.07.2010
boek